Lipoprotein apheresis for lipoprotein(a)-associated cardiovascular disease: prospective 5 years of follow-up and apolipoprotein(a) characterization - Röseler, Eberhard; März, Winfried (Arteriosclerosis, thrombosis, and vascular biology, 2016)
Objective—Lipoprotein(a)-hyperlipoproteinemia (Lp(a)-HLP) along with progressive cardiovascular disease has been approved as indication for regular lipoprotein apheresis (LA) in Germany since 2008. We aimed to study the long-term preventive effect of LA and to assess hypothetical clinical correlations of apolipoprotein(a) (apo(a)) by analyzing genotypes and phenotypes.Approach and Results—This prospective observational multicenter study included 170 patients with Lp(a)-HLP and progressive cardiovascular disease (48.9 years median age at diagnosis) despite other cardiovascular risk factors, including low-density lipoprotein cholesterol had maximally been treated (mean baseline low-density lipoprotein cholesterol: measured, 2.56 mmol/L [98.9 mg/dL] and corrected, 1.72 mmol/L [66.3 mg/dL]). Patients were prospectively investigated during a 5-year period about annual incidence rates of cardiovascular events. In addition, apo(a) isoforms and polymorphisms at the apo(a) gene (LPA) were characterized. One hundred fifty-four patients (90.6%) completed 5 years of follow-up. Mean Lp(a) concentration before commencing regular LA was 108.1 mg/dL. This was reduced by a single LA treatment by 68.1% on average. Significant decline of the mean annual cardiovascular event rate was observed from 0.58±0.53 2 years before regular LA to 0.11±0.15 thereafter (P<0.0001); 95.3% of patients expressed at least 1 small apo(a) isoform. Small apo(a) isoform (35.2%) carrying phenotypes were not tagged by single-nucleotide polymorphisms rs10455872 or rs3798220.Conclusions—Results of 5 years of prospective follow-up confirm that LA has a lasting effect on prevention of cardiovascular events in patients with Lp(a)-HLP. Patients clinically selected by progressive cardiovascular disease were characterized by a highly frequent expression of small apo(a) isoforms. Only Lp(a) concentration seemed to comprehensively reflect Lp(a)-associated cardiovascular risk, however.